Demolition Blues. Resistance Against Demolition Plans in a Danish Disadvantaged Affordable Housing Estate - Jonas Strandholdt Bach (Archivio Antropologico Mediterraneo)
The affordable housing estate Gellerup in Aarhus, Denmark, has been under transformation for the past eight years. Since the final adoption in 2011 of a Master Plan, implemented by the housing association running the estate and the Municipality in close cooperation, demolitions, infrastructural projects, and new constructions have been the order of the day. New national political discussions in 2018 opened for local discussions on the future of the estate, resulting in a City Council decision to work towards further demolitions and transformations than initially agreed upon. The City Council decision aims at creating a different social mix in the estate by removing affordable housing units and building owner-occupied and private rental units, attracting affluent citizens. The decision resulted in various responses from current residents. Here I will examine two forms of “resistance” – outright protest and relocation. I relate the two cases to the ongoing development of the estate and issues of planning and the construction of a particular future for the estate. The article is based on ethnographic research conducted from 2015 to 2019.